Extracorporeal Membrane Oxygenation Induces Short-Term Loss of High-Molecular-Weight von Willebrand Factor Multimers. (April 2015) - Tauber, Helmuth; Ott, Helmut; Streif, Werner; Weigel, Guenter; Loacker, Lorin; Fritz, Josef; Heinz, Anneliese; Velik-Salchner, Corinna
<x xml:space="preserve">Abstract</x> BACKGROUND: High-molecular-weight (HMW) von Willebrand factor (vWF) multimers are crucial for primary hemostasis. Increased shear stress from ventricular assist devices can provoke premature degradation of HMW vWF multimers. Whether similar loss of vWF multimers occurs during extracorporeal membrane oxygenation (ECMO) is not clear. METHODS: We conducted a prospective observational study in a clinical cohort of patients who required ECMO for intractable cardiac and/or respiratory failure. The primary end point was the quantity and quality of HMW vWF multimer bands before, during, and after ECMO support. To investigate further changes in primary hemostasis, we also measured vWF antigen activity (vWF:Ag), vWF ristocetin cofactor activity (vWF:RCo), and factor VIII in 38 patients who required ECMO support before initiation of ECMO (baseline), after 24 and 48 hours on ECMO, and 24 hours after termination of ECMO therapy. RESULTS: Compared with baseline, vWF:Ag and vWF:RCo decreased after 24 hours of ECMO (mean ± SD, vWF:Ag, 307% ± 152% to 261% ± 138%, P = 0.002; vWF:RCo 282% ± 145% to 157% ± 103%, P < 0.0001) and remained lower during ongoing support (vWF:Ag 265% ± 128%, P = 0.025; vWF:RCo 163% ± 94%, P < 0.0001). After termination of ECMO, vWF:Ag was greater than baseline (359% ± 131%, P = 0.004) and vWF:RCo was similar to baseline levels (338% ± 142%, P = 0.046). Compared with baseline, the calculated vWF:RCo/vWF:Ag ratio decreased after 24 hours on support (0.96 ± 0.23 to 0.61 ± 0.17, P ⩽ 0.0001) and remained lower during 48 hours on ECMO (0.63 ± 0.18, P ⩽ 0.0001). After termination of ECMO support (0.94 ± 0.19, P = 0.437), values rapidly returned to baseline. The number of HMW vWF multimers (n) decreased from baseline after 24 hours on ECMO (21 ± 1.4 to 14 ± 1.8, P ⩽ 0.0001) and after 48 hours on ECMO (15 ± 2.1, P ⩽ 0.0001). Twenty-four hours after termination of ECMO support, HMW vWF multimeric pattern had returned to baseline values (21 ± 1.8, P = 0.551). CONCLUSIONS: Loss of HMW vWF multimer bands occurred in patients undergoing ECMO support and resolved after the termination of ECMO. Although not detectable with coagulation screening tests, a vWF:RCo/vWF:Ag ratio <0.7 during ECMO was highly indicative for loss of HMW vWF multimers. Our findings may at least in part explain increased bleeding tendency during ECMO therapy. Administration of vWF concentrates may support restoration of primary hemostasis in patients with relevant bleeding during ECMO support.